Uma solução para integração de ambientes virtuais de aprendizagem com Blockchain (Research, Society and Development, 2021)
Education generates a considerable amount of data and information, it is necessary to manage this data securely, avoiding problems of falsification and tampering with diplomas, certificates, and other important student documents. In addition, distance learning is becoming more popular due to the Covid-19 pandemic period, where courses are offered in virtual learning environments such as Moodle. Blockchain technology can be used as a tool to ensure the security of data managed by Moodle. However, there is a gap in current state-of-the-art solutions for integrating these data with Blockchain platforms. This work proposes BlockMoodle, a solution developed to integrate Moodle with Blockchain Ethereum. This work also performs an analysis of the financial cost of using the tool. In addition, a performance evaluation of the proposed solution is also carried out considering different usage scenarios. Finally, the conclusions and future work to be developed are presented.